Properties of the Pc(4312) pentaquark and its bottom partner. (May 2021) - Azizi, K.; Sarac, Y.; Sundu, H.
Abstract: We present an analysis of the newly observed pentaquark to shed light on its quantum numbers. To do that, the QCD sum rules approach is used. The measured mass of this particle is close to the threshold and has a small width, which supports the possibility of its being a molecular state. We consider an interpolating current in a molecular form and analyze both the positive and negative parity states with spin- . We also consider the bottom counterpart of the state with similar molecular form. Our mass result for the charm pentaquark state supports that the quantum numbers of the observed state are consistent with .